Periostin and CA242 as potential diagnostic serum biomarkers complementing CA19.9 in detecting pancreatic cancer. Issue 9 (24th July 2018) - Dong, Dong; Jia, Li; Zhang, Lufang; Ma, Na; Zhang, Aimin; Zhou, Yunli; Ren, Li
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor with few biomarkers to guide treatment options. Carbohydrate antigen 19.9 (CA19.9), the most frequently used biomarker for PDAC, is not sensitive and specific enough for the detection of the disease. This study aimed to evaluate serum periostin (POSTN) and CA242 as potential diagnostic biomarkers complementing CA19.9 in detecting pancreatic cancer. Blood samples were from 362 participants, including 213 patients with different stages of PDAC, 75 patients with benign pancreatic disease, and 74 healthy individuals. All samples were randomly divided into a training set and a validation set. Carbohydrate antigen 19.9, CA242, POSTN, as well as carcinoembryonic antigen, were measured by ELISA or automated immunoassay. The receiver operating characteristic curve analysis revealed that the performance of CA19.9 in the validation group were improved by the marker panel composed of CA19.9, POSTN, and CA242, to discriminate early stage PDAC not only from healthy controls (area under the curve [AUC]CA19.9 = 0.94 vs AUCCA19.9 + POSTN + CA242 = 0.98, P < .05) but also from benign conditions (AUCCA19.9 = 0.87 vs AUCCA19.9 + POSTN + CA242 = 0.90, P < .05). In addition, POSTN retained significant diagnostic capabilities to distinguish PDAC CA19.9‐negative from healthy controls (AUCPOSTN = 0.87) as well as from benign conditions (AUCPOSTN = 0.84) in the whole set. This study suggested that POSTN and CA242 are potential diagnostic serum biomarkers complementing CA19.9 in detecting early pancreatic cancer. Abstract : Serum levels of periostin (POSTN) were significantly increased in patients with pancreatic ductal adenocarcinoma (PDAC). Performances of carbohydrate antigen 19.9 (CA19.9) were improved by the marker panel composed of CA19.9, POSTN, and CA242, to discriminate early stage PDAC from control subjects. POSTN retained significant diagnostic capabilities to distinguish CA19.9‐negative PDAC from control subjects.